2012
DOI: 10.4137/bmi.s9415
|View full text |Cite
|
Sign up to set email alerts
|

Serological Investigation of the Collagen Degradation Profile of Patients with Chronic Obstructive Pulmonary Disease or Idiopathic Pulmonary Fibrosis

Abstract: In both chronic obstructive pulmonary disease (COPD) and idiopathic pulmonary fibrosis (IPF), abnormally high collagen remodeling occurs within the lung tissue. Matrix metalloproteinase (MMP)-degraded type I, III, IV, V and VI collagen and a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS)-degraded type III collagen were assessed in serum of patients diagnosed with mild COPD (n = 10) or IPF (n = 30), and healthy controls (n = 15). The collagen degradation markers C1M, C3M, C5M and C6M were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 54 publications
2
57
1
3
Order By: Relevance
“…It is possible that the high levels of C1M, C4M, and VICM in the blood are results of a systemic effect where subjects with a general increased remodeling of the ECM and IF have a higher likelihood of developing cancer. Furthermore, all markers have been found elevated in a number of diseases characterized by ECM remodeling and tissue inflammation and are, therefore, not specific to cancer (7)(8)(9)(36)(37)(38)(39). Finally, it needs to be elucidated if the results of this study can be applied to populations of other ages and ethnic backgrounds and if the biomarkers are more useful for certain types of solid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the high levels of C1M, C4M, and VICM in the blood are results of a systemic effect where subjects with a general increased remodeling of the ECM and IF have a higher likelihood of developing cancer. Furthermore, all markers have been found elevated in a number of diseases characterized by ECM remodeling and tissue inflammation and are, therefore, not specific to cancer (7)(8)(9)(36)(37)(38)(39). Finally, it needs to be elucidated if the results of this study can be applied to populations of other ages and ethnic backgrounds and if the biomarkers are more useful for certain types of solid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Col-VI spiked some attention due to its selective expression in some fibrotic conditions (i.e., kidney and myocardial fibrosis) as well as in hepatocellular carcinoma (136). In fact, its level of expression has been recently proposed to serve as a clinical prognostic marker (204,205). Carcinomas that typically present an aggressive progression (i.e., liver and pancreas) are characterized by a large deposition of interstitial FN and collagen.…”
Section: Collagenmentioning
confidence: 99%
“…These neoepitopes have been shown to be more accurate diagnostic and prognostic markers for individual fibroproliferative diseases than their protein of origin 10,11 . Previous small point-of-diagnosis studies have suggested that matrix neoepitopes may be elevated in individuals with IPF compared with healthy controls [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%